Practicing Courage in a Communal Key. Issue 2 (17th August 2018) - Stengel, Barbara S.
Abstract: Barbara Stengel's purpose in this essay is to complicate our understanding of the quality and status of educational courage as it is typically exercised in schools today, and to offer profiles of that courage in a minor key. If we only portray — and aspire to — courage in the heroic form that tilts against a system that is unfair, misguided, or both, we may fail to recognize that courage is practiced in the communal construction of action spaces that make the heroic form unnecessary. In building her argument, Stengel examines the calls for and descriptions of educational courage today; looks to Aristotle, Hans Georg Gadamer, and John Dewey for advice about how to approach courage as embodied, created in interaction, expressed as habit, and engendering responsibility; and then describes two sets of teachers she holds up as collective examples worthy of our consideration. In the process, Stengel stakes a claim for this view of courage in education in a minor key, one that is (more) contemporary, critical, inclusive, democratic, and communal.